A magnesium-cobalt modified ferromanganese phosphate precursor material and its preparation method and application, carbon-coated lithium ferromanganese phosphate positive electrode material and its application

By modifying ferromanganese phosphate precursor material with magnesium-cobalt, the problems of low conductivity and poor structural stability of ferromanganese phosphate precursor material in the prior art are solved, and the effect of improving the electrochemical performance of lithium ferromanganese phosphate material and the circulation performance of lithium ion batteries is achieved.

CN119750528APending Publication Date: 2025-04-04GANFENG LITHIUM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411943578.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The ferromanganese phosphate precursor materials prepared in the prior art have low conductivity and large interface charge transfer resistance, and Jahn-Teller distortion caused by Mn element leads to collapse of the material structure and high inactivation rate.

Method used

By modifying ferromanganese phosphate precursor material by magnesium-cobalt, magnesium-cobalt is doped at the iron site in the ferromanganese phosphate matrix, or magnesium is doped at the iron site, and cobalt is coated on the outer layer to increase the interface charge transfer rate and avoid structural distortion.

Benefits of technology

The stability and electrochemical performance of lithium manganese iron phosphate material are improved, the stability of the material during the charging and discharging process is enhanced, and the conductivity is improved through carbon coating, which improves the circulation and rate performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750528A_ABST
    Figure CN119750528A_ABST
Patent Text Reader

Abstract

The present invention provides a magnesium-cobalt modified ferromanganese phosphate precursor material, a preparation method and application thereof, a carbon-coated lithium ferromanganese phosphate positive electrode material and application thereof, and belongs to the technical field of lithium ion batteries. The magnesium-cobalt modified ferromanganese phosphate precursor material of the present invention comprises a ferromanganese phosphate matrix and magnesium-cobalt elements; the magnesium-cobalt elements are doped in the iron element sites in the ferromanganese phosphate matrix, or the magnesium elements are doped in the iron element sites in the ferromanganese phosphate matrix and the cobalt elements are coated on the outer layer of the ferromanganese phosphate matrix. The present invention introduces magnesium-cobalt into the ferromanganese phosphate precursor to replace part of the ferrous ion lattice, or coats a cobalt layer on the outer layer of the magnesium-doped precursor, which can adjust the electronic structure of the material and achieve a faster electrochemical redox reaction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a magnesium-cobalt modified ferromanganese phosphate precursor material, a preparation method and application thereof, and a carbon-coated lithium ferromanganese phosphate positive electrode material and application thereof. Background Art

[0002] Since 1991, lithium-ion batteries have been using transition metal oxides as the main source of cathode materials. However, these materials release oxygen in highly delithiated oxides, resulting in poor thermal stability. 4 (M=Fe, Mn, Co and Ni, etc.) has attracted a lot of attention due to its advantages over layered cathode materials such as structural stability, cost-effectiveness and environmental friendliness, and is considered to be the most promising cathode material for lithium-ion batteries. Among them, lithium iron phosphate (LiFePO 4 Lithium manganese phosphate (LFP) has been widely used in the field of lithium batteries because of its advantages of low price, environmental friendliness, high safety performance, good structural stability and cycle performance. However, the low operating voltage (3.4V) and energy density (580Wh / kg) of LFP have severely restricted the development of LFP. Compared with LFP, lithium manganese phosphate (LiMnPO 4 , referred to as LMP) has a higher working voltage (4.1V) and energy density (701Wh / kg). However, LMP has extremely low conductivity and Li + Diffusion coefficient, Mn 3+ The resulting Jahn-Teller distortion (manganese precipitation problem) will also affect the structural stability and limit the application of LMP.

[0003] Lithium iron manganese phosphate (LiMn x Fe 1-x PO 4, abbreviated as LMFP) belongs to the product of the mixed doping of lithium iron phosphate and lithium manganese phosphate, and has the same structure as lithium iron phosphate, both of which are ordered and regular olivine structures. LMFP combines the advantages of the high working voltage of LMP and the good kinetic performance of LFP, while reducing the usage of metal sources, lowering the manufacturing cost, and is also known as the "upgraded version of lithium iron phosphate". The preparation route of lithium manganese iron phosphate is similar to that of lithium iron phosphate, and its preparation methods also include two categories: solid-phase method and liquid-phase method. The principle of the method is to mix lithium compounds, iron compounds, phosphorus compounds, and manganese compounds and react under specific conditions. The solid-phase method includes high-temperature solid-phase method, carbothermal reduction method, etc., and the liquid-phase method includes solvothermal method, sol-gel method, co-precipitation method, etc. The solid-phase method has relatively simple process and is the current mainstream large-scale synthesis method. Although the solid-phase method has a simple process, due to the uneven mixing of raw materials, it is easy to lead to an increase in the subsequent calcination time and uneven surface activity distribution, resulting in uneven particles. The products obtained by the liquid-phase method have high consistency, but their equipment and processes are relatively complex, the preparation cost is high, and it is difficult to achieve large-scale industrial production.

[0004] Lithium manganese iron phosphate is expected to become the cathode material of the new generation of high-energy density power batteries, and its precursor iron manganese phosphate ((Mn x Fe 1-x ) 3 (PO 4 ) 2 , 0 < x < 1) has also received increasing attention. The performance indicators such as the composition, structure, particle size, and morphology of iron manganese phosphate play a crucial role in the electrochemical performance of the synthesized lithium manganese iron phosphate material. However, the iron manganese phosphate precursor prepared by the existing technology has a low conductivity and a large interfacial charge transfer resistance. At the same time, the Jahn-Teller distortion brought by the Mn element will accelerate the collapse of the material structure, resulting in the inactivation of the material. Summary of the Invention

[0005] The purpose of the present invention is to provide a magnesium-cobalt modified iron manganese phosphate precursor material, its preparation method and application, a carbon-coated lithium manganese iron phosphate cathode material and its application. The present invention modifies iron manganese phosphate with magnesium and cobalt, which can improve the interfacial charge transfer rate and avoid structural distortion, thereby enhancing the stability and electrochemical performance of the subsequent calcined lithium manganese iron phosphate.

[0006] In order to achieve the above invention purpose, the present invention provides the following technical solutions:

[0007] The present invention provides a magnesium-cobalt modified iron manganese phosphate precursor material, including an iron manganese phosphate matrix and magnesium and cobalt elements; the magnesium and cobalt elements are doped at the iron element sites of the iron manganese phosphate matrix, or the magnesium element is doped at the iron element sites of the iron manganese phosphate matrix and the cobalt element is coated on the outer layer of the iron manganese phosphate matrix.

[0008] The present invention provides a method for preparing the magnesium-cobalt modified ferromanganese phosphate precursor material described in the above technical solution, comprising the following steps:

[0009] Mixing a metal source, an antioxidant and water to obtain a first solution; mixing a phosphorus source and water to obtain a second solution;

[0010] The first solution, the second solution and an alkali solution are mixed to carry out a liquid phase coprecipitation reaction, and then aged to obtain a precursor slurry;

[0011] Drying the precursor slurry to obtain a magnesium-cobalt modified ferromanganese phosphate precursor material;

[0012] The metal source is a manganese source, a ferrous source, a magnesium source and a first cobalt source; or the metal source is a manganese source, a ferrous source and a magnesium source;

[0013] When the metal source is a manganese source, a ferrous source and a magnesium source, after the precursor slurry is dried, the dried precursor is mixed with a second cobalt source, and annealed under a protective atmosphere to obtain a magnesium-cobalt modified manganese ferrophosphate precursor material.

[0014] Preferably, the manganese source includes at least one of manganese sulfate, manganese chloride, manganese nitrate and manganese acetate;

[0015] The ferrous source includes at least one of ferrous sulfate, ferrous oxalate and ferrous chloride;

[0016] The magnesium source includes at least one of magnesium chloride and magnesium sulfate;

[0017] The first cobalt source includes at least one of cobalt sulfate, cobalt chloride and cobalt nitrate;

[0018] The second cobalt source includes at least one of cobalt oxide and cobalt tetroxide;

[0019] The antioxidant comprises at least one of ascorbic acid, ascorbyl palmitate, erythorbic acid and sodium erythorbate;

[0020] The phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate and diammonium dihydrogen phosphate;

[0021] The molar ratio of the manganese source, the ferrous source, the magnesium source, the first cobalt source and the antioxidant is 2-8:1.7-7.9:0.1-0.3:0.1-0.3:1; the molar ratio of the manganese source, the ferrous source, the magnesium source, the second cobalt source and the antioxidant is 2-8:1.7-7.9:0.1-0.3:0.1-0.3:1;

[0022] The molar ratio of the phosphorus source to the total moles of the manganese source, the ferrous source, the magnesium source and the first cobalt source is 1.1 to 1.3:1;

[0023] The molar ratio of the phosphorus source to the total moles of the manganese source, the ferrous source, the magnesium source and the second cobalt source is 1.1-1.3:1.

[0024] Preferably, the temperature of the liquid phase coprecipitation reaction is 50-90° C., the pH value is 5-7, and the aging time is 2-4 hours.

[0025] Preferably, the drying method is vacuum drying, the drying temperature is 80-110° C., and the drying time is 12-24 hours;

[0026] The annealing temperature is 350-550° C., the holding time is 4-6 hours, and the heating rate to the annealing temperature is 5-10° C. / min.

[0027] The present invention provides the use of the magnesium-cobalt modified ferromanganese phosphate precursor material described in the above technical solution or the magnesium-cobalt modified ferromanganese phosphate precursor material prepared by the preparation method described in the above technical solution in lithium iron manganese phosphate positive electrode materials.

[0028] The present invention provides a carbon-coated lithium manganese iron phosphate positive electrode material, and the preparation method comprises the following steps:

[0029] The magnesium-cobalt modified manganese iron phosphate precursor material is mixed with a lithium source, a phosphorus compound and a carbon source, and calcined under a protective atmosphere to obtain a carbon-coated manganese iron lithium phosphate positive electrode material;

[0030] The magnesium-cobalt modified ferromanganese phosphate precursor material provided by the present invention is the magnesium-cobalt modified ferromanganese phosphate precursor material described in the above technical solution or the magnesium-cobalt modified ferromanganese phosphate precursor material prepared by the preparation method described in the above technical solution.

[0031] Preferably, the lithium source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium hydroxide, lithium carbonate, lithium acetate and lithium oxalate, the phosphorus compound includes lithium phosphate or lithium dihydrogen phosphate, and the carbon source includes at least one of glucose, sucrose, citric acid, polyvinyl pyrrolidone, polyethylene glycol and ascorbic acid;

[0032] The molar ratio of the magnesium-cobalt modified ferromanganese phosphate precursor material to the lithium source, the phosphorus compound and the carbon source is 1:(0.85-1.15):(0.85-1.15):(0.15-0.35);

[0033] The mixing method is ball milling, the rotation speed of the ball mill is 350-500 rpm, and the ball milling time is 1.5-2.5 h;

[0034] Preferably, the calcination includes a first calcination and a second calcination performed sequentially; the temperature of the first calcination is 300-500°C, and the insulation time is 4-6 hours; the temperature of the second calcination is 550-750°C, and the insulation time is 10-12 hours; the heating rates for the first calcination and the second calcination are independently 5-10°C / min.

[0035] The present invention provides the use of the carbon-coated lithium manganese iron phosphate positive electrode material described in the above technical solution in a lithium ion battery.

[0036] The present invention provides a magnesium-cobalt modified ferromanganese phosphate precursor material. The present invention introduces magnesium-cobalt to replace the lattice of part of the ferrous ions in the ferromanganese phosphate precursor, or coats the outer layer of the magnesium-doped precursor with a cobalt layer. Magnesium and cobalt are doped cations of the same valence, which can improve the reaction kinetics of lithium iron manganese phosphate without losing energy density, and the doping of cations of the same valence does not involve a charge compensation mechanism and will not affect the crystal structure of the material. Therefore, the synergistic effect of magnesium-cobalt co-modification can greatly improve the stability of olivine structure materials during charging and discharging, and at the same time can adjust the electronic structure of the material to achieve a faster electrochemical redox reaction process. Compared with the addition of magnesium / cobalt in the subsequent firing process of carbon-coated lithium iron manganese phosphate, the present invention can achieve coexistence at the molecular level, which is more conducive to improving electrochemical performance, and can be applied to amorphous carbon-coated lithium iron manganese phosphate, a positive electrode material of lithium ion batteries.

[0037] The primary particle size of the positive electrode material prepared by using the magnesium-cobalt modified ferromanganese phosphate precursor material of the present invention can reach the nanometer level, and self-assemble into a micron-sphere morphology, with a high specific surface area, wherein lithium ions migrate along the short axis, reducing the diffusion distance of lithium ions, improving ion conductivity and structural stability, and carbon coating through two calcinations to greatly improve the conductivity of the material. When applied to lithium-ion batteries, the cycle performance and rate performance of the lithium-ion batteries are further improved.

[0038] The preparation process of the invention is simple and easy to operate, has low cost, does not use a sand mill for mixing, greatly reduces production cost, is environmentally friendly, has excellent electrical properties, and can achieve large-scale industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a SEM image of the magnesium-cobalt modified ferromanganese phosphate precursor obtained in Example 1;

[0040] Figure 2 This is a SEM image of the carbon-coated lithium manganese iron phosphate obtained in Example 1;

[0041] Figure 3 This is the XRD pattern of the carbon-coated lithium manganese iron phosphate obtained in Example 1. DETAILED DESCRIPTION

[0042] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0043] The present invention provides a magnesium-cobalt modified ferromanganese phosphate precursor material, comprising a ferromanganese phosphate matrix and magnesium and cobalt elements; the magnesium and cobalt elements are doped into the iron element sites in the ferromanganese phosphate matrix, or the magnesium element is doped into the iron element sites in the ferromanganese phosphate matrix and the cobalt element is coated on the outer layer of the ferromanganese phosphate matrix.

[0044] When the magnesium element is doped into the iron site in the ferromanganese phosphate matrix and the cobalt element is coated on the outer layer of the ferromanganese phosphate matrix, the magnesium element replaces the iron site doping through a liquid phase coprecipitation method, and the cobalt element is coated on the outer layer of the ferromanganese phosphate matrix through a solid phase method.

[0045] When the magnesium and cobalt elements are doped into the iron site in the ferromanganese phosphate matrix, the magnesium and cobalt elements are doped in place of the iron site by a liquid phase coprecipitation method.

[0046] The present invention provides a method for preparing the magnesium-cobalt modified ferromanganese phosphate precursor material described in the above technical solution, comprising the following steps:

[0047] Mixing a metal source, an antioxidant and water to obtain a first solution; mixing a phosphorus source and water to obtain a second solution;

[0048] The first solution, the second solution and an alkali solution are mixed to carry out a liquid phase coprecipitation reaction, and then aged to obtain a precursor slurry;

[0049] Drying the precursor slurry to obtain a magnesium-cobalt modified ferromanganese phosphate precursor material;

[0050] The metal source is a manganese source, a ferrous source, a magnesium source and a first cobalt source; or the metal source is a manganese source, a ferrous source and a magnesium source;

[0051] When the metal source is a manganese source, a ferrous source and a magnesium source, after the precursor slurry is dried, the dried precursor is mixed with a second cobalt source, and annealed under a protective atmosphere to obtain a magnesium-cobalt modified manganese ferrophosphate precursor material.

[0052] In the present invention, the manganese source preferably includes at least one of manganese sulfate, manganese chloride, manganese nitrate and manganese acetate; the ferrous source preferably includes at least one of ferrous sulfate, ferrous oxalate and ferrous chloride; the magnesium source preferably includes at least one of magnesium chloride and magnesium sulfate; the first cobalt source preferably includes at least one of cobalt sulfate, cobalt chloride and cobalt nitrate; the second cobalt source preferably includes at least one of cobalt oxide and cobalt tetraoxide; the phosphorus source preferably includes at least one of phosphoric acid, diammonium hydrogen phosphate and ammonium dihydrogen phosphate; the antioxidant preferably includes at least one of ascorbic acid, ascorbyl palmitate, isoascorbic acid and sodium isoascorbate. When the manganese source, ferrous source, magnesium source, phosphorus source, first cobalt source, second cobalt source or antioxidant are two or more of the above, the present invention has no special limitation on the amount of different types of raw materials, and any ratio is acceptable.

[0053] In the present invention, the manganese source is more preferably manganese chloride; the iron source is more preferably ferrous sulfate; the magnesium source is more preferably magnesium sulfate; the first cobalt source is more preferably cobalt sulfate; the antioxidant is more preferably ascorbic acid; and the phosphorus source is more preferably phosphoric acid.

[0054] In the present invention, the molar ratio of the manganese source, the ferrous source, the magnesium source, the first cobalt source and the antioxidant is preferably 2-8:1.7-7.9:0.1-0.3:0.1-0.3:1, and more preferably 4-6:3.8:0.2:0.1:1; the molar ratio of the manganese source, the ferrous source, the magnesium source, the second cobalt source and the antioxidant is preferably 2-8:1.7-7.9:0.1-0.3:0.1-0.3:1, and more preferably 6:3.8:0.2:0.1-0.25:1.

[0055] In the present invention, the molar ratio of the phosphorus source to the total molar ratio of the manganese source, the ferrous source, the magnesium source and the first cobalt source is preferably 1.1-1.3:1, more preferably 1.2-1.28:1; the molar ratio of the phosphorus source to the total molar ratio of the manganese source, the ferrous source, the magnesium source and the second cobalt source is preferably 1.1-1.3:1, more preferably 1.18-1.2:1.

[0056] In the present invention, the first solution and the second solution are preferably added dropwise to the reactor respectively, and an alkali solution is added to adjust the pH value to carry out a liquid phase coprecipitation reaction; the flow rate of the dropwise addition is preferably 10 to 30 mL / min, more preferably 20 to 25 mL / min.

[0057] In the present invention, the alkali solution is preferably ammonia water, and the concentration of the ammonia water is preferably 20% to 40%, more preferably 25%. The amount of the alkali solution used in the present invention is preferably sufficient to achieve the pH value required for the liquid phase coprecipitation reaction.

[0058] In the present invention, the temperature of the liquid phase coprecipitation reaction is preferably 50-90°C, more preferably 70-80°C, the pH value is preferably 5-7, more preferably 6-6.5; the aging time is preferably 2-4h, more preferably 2h.

[0059] After the aging is completed, the present invention preferably washes and filters the obtained slurry to obtain a precursor slurry.

[0060] In the present invention, the drying method is preferably vacuum drying, the drying temperature is preferably 80 to 110° C., the drying time is preferably 12 to 24 hours, and more preferably 18 hours.

[0061] In the present invention, when the metal source is a manganese source, a ferrous source and a magnesium source, after the precursor slurry is dried, the dried precursor is mixed with a second cobalt source and annealed under a protective atmosphere to obtain a magnesium-cobalt modified manganese ferrophosphate precursor material; the annealing temperature is preferably 350 to 550°C, more preferably 450°C; the holding time is preferably 4 to 6h, more preferably 5h, and the heating rate to the annealing temperature is preferably 5 to 10°C / min; the protective atmosphere is preferably nitrogen, argon or helium.

[0062] The present invention adopts a coprecipitation method to prepare a magnesium-cobalt modified manganese iron phosphate precursor, wherein manganese and iron exist in the form of divalent ions, and the anion is a phosphate radical. As a precursor, there is no need to perform a reduction process during the subsequent sintering of carbon-coated manganese iron lithium phosphate. Compared with the traditional solid phase method, the reduction process is omitted, and the structural defects caused by the reduction of Mn and Fe during the preparation process are reduced. Moreover, compared with the conventional solid phase sintering method, the manganese iron in the precursor prepared by the coprecipitation method can achieve atomic / molecular mixing, and magnesium and cobalt are introduced into the precursor at the same time, which maximizes the positive synergistic effect of doping or coating metal ions on the electrical properties of the material.

[0063] The present invention provides the use of the magnesium-cobalt modified ferromanganese phosphate precursor material described in the above technical solution or the magnesium-cobalt modified ferromanganese phosphate precursor material prepared by the preparation method described in the above technical solution in lithium iron manganese phosphate positive electrode materials.

[0064] The present invention provides a carbon-coated lithium manganese iron phosphate positive electrode material, and the preparation method comprises the following steps:

[0065] The magnesium-cobalt modified manganese iron phosphate precursor material is mixed with a lithium source, a phosphorus compound and a carbon source, and calcined under a protective atmosphere to obtain a carbon-coated manganese iron lithium phosphate positive electrode material;

[0066] The magnesium-cobalt modified ferromanganese phosphate precursor material provided by the present invention is the magnesium-cobalt modified ferromanganese phosphate precursor material described in the above technical solution or the magnesium-cobalt modified ferromanganese phosphate precursor material prepared by the preparation method described in the above technical solution.

[0067] In the present invention, the lithium source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium hydroxide, lithium carbonate, lithium acetate and lithium oxalate; the phosphorus compound includes lithium phosphate or lithium dihydrogen phosphate, and the carbon source includes at least one of glucose, sucrose, citric acid, polyvinyl pyrrolidone, polyethylene glycol and ascorbic acid; when the lithium source, phosphorus compound or carbon source is two or more of the above, the present invention has no special limitation on the ratio of different types of carbon sources, and any ratio is acceptable.

[0068] In the present invention, the lithium source is more preferably lithium dihydrogen phosphate and lithium carbonate, the phosphorus compound is more preferably lithium dihydrogen phosphate, and the carbon source is more preferably sucrose.

[0069] In the present invention, the molar ratio of the magnesium-cobalt modified manganese ferrophosphate precursor material to the lithium source, the phosphorus compound and the carbon source is preferably 1:(0.85-1.15):(0.85-1.15):(0.15-0.35), more preferably 1:(0.9-1.1):(0.9-1.1):(0.15-0.3), and further preferably 1:1:1:0.2-0.25.

[0070] In the present invention, the mixing method is preferably ball milling, the rotation speed of the ball mill is preferably 350-500 rpm, more preferably 400 rpm; the ball milling time is preferably 1.5-2.5 h, more preferably 2 h;

[0071] In the present invention, the protective atmosphere is preferably nitrogen, argon or helium.

[0072] In the present invention, the calcination preferably includes a first calcination and a second calcination carried out sequentially; the temperature of the first calcination is preferably 300-500°C, more preferably 350-450°C, further preferably 400°C, and the holding time is preferably 4-6h, more preferably 4-5h; the temperature of the second calcination is preferably 550-750°C, more preferably 600-650°C, and the holding time is preferably 10-12h; the heating rates for heating to the first calcination and the second calcination are independently preferably 5-10°C / min.

[0073] The present invention provides the application of the carbon-coated lithium manganese iron phosphate positive electrode material in the above technical solution in a lithium ion battery. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0074] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0075] Example 1

[0076] This embodiment provides a method for preparing a magnesium-cobalt modified ferromanganese phosphate precursor and a carbon-coated lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0077] Step (1): according to the concentrations of the raw materials in the first solution being 0.3 mol / L manganese chloride, 0.19 mol / L ferrous sulfate, 0.01 mol / L magnesium sulfate, 0.005 mol / L cobalt sulfate and 0.05 mol / L ascorbic acid, the raw materials are uniformly dispersed in water to obtain a first solution, and 85 wt.% phosphoric acid is uniformly dispersed in water to obtain a second solution with a concentration of 0.4 mol / L;

[0078] Step (2): 400 mL of the first solution and 606 mL of the second solution were respectively dripped into the reactor for a co-precipitation reaction at a constant temperature of 50° C. The flow rate of the first solution and the second solution was 25 mL / min. The pH of the reaction system was regulated to 6.5 by ammonia water (mass concentration 25%), and aged for 2 h to obtain a precursor slurry;

[0079] Step (3): washing and filtering the precursor slurry, and vacuum drying at 110° C. for 18 h to obtain a magnesium-cobalt modified ferromanganese phosphate precursor;

[0080] Step (4): 0.1 mol of the magnesium-cobalt modified manganese iron phosphate precursor and 0.1 mol of lithium dihydrogen phosphate, 0.1 mol of lithium carbonate and 0.02 mol of sucrose are mixed evenly by ball milling at 400 rpm / 2h and placed in a tubular furnace for calcination in two stages under an argon atmosphere, wherein the first calcination temperature is 350°C and the holding time is 4h, the second calcination temperature is 650°C and the holding time is 12h, and the heating rates of the two heatings are both 5°C / min, to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.

[0081] Example 2

[0082] This embodiment provides a method for preparing a magnesium-cobalt modified ferromanganese phosphate precursor and a carbon-coated lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0083] Step (1): according to the concentrations of the raw materials in the first solution being 0.4 mol / L manganese chloride, 0.09 mol / L ferrous sulfate, 0.01 mol / L magnesium sulfate, 0.005 mol / L cobalt sulfate and 0.05 mol / L ascorbic acid, the raw materials are uniformly dispersed in water to obtain a first solution, and 85 wt.% phosphoric acid is uniformly dispersed in water to obtain a second solution with a concentration of 0.4 mol / L;

[0084] Step (2): 400 mL of the first solution and 650 mL of the second solution were respectively dripped into the reactor for a co-precipitation reaction at a constant temperature of 70°C. The flow rate of the first solution and the second solution was 30 mL / min. The pH of the reaction system was adjusted to 6 by ammonia water (mass concentration 25%), and the precursor slurry was obtained after aging for 2 hours.

[0085] Step (3): washing and filtering the precursor slurry, and vacuum drying at 110° C. for 18 h to obtain a magnesium-cobalt modified ferromanganese phosphate precursor;

[0086] Step (4): 0.1 mol of the magnesium-cobalt modified manganese iron phosphate precursor and 0.09 mol of lithium dihydrogen phosphate, 0.11 mol of lithium carbonate and 0.025 mol of sucrose are mixed evenly by ball milling at 400 rpm / 2h, and then placed in a tubular furnace for calcination in two stages under an argon atmosphere, wherein the first calcination temperature is 400°C and the holding time is 5h, the second calcination temperature is 600°C and the holding time is 12h, and the heating rates of the two heatings are both 5°C / min, to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.

[0087] Example 3

[0088] This embodiment provides a method for preparing a magnesium-cobalt modified ferromanganese phosphate precursor and a carbon-coated lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0089] Step (1): according to the concentrations of the raw materials in the first solution being 0.2 mol / L manganese chloride, 0.19 mol / L ferrous sulfate, 0.01 mol / L magnesium sulfate, 0.005 mol / L cobalt sulfate and 0.05 mol / L ascorbic acid, the raw materials are uniformly dispersed in water to obtain a first solution, and 85 wt.% phosphoric acid is uniformly dispersed in water to obtain a second solution with a concentration of 0.4 mol / L;

[0090] Step (2): 400 mL of the first solution and 500 mL of the second solution were respectively dripped into the reactor for a co-precipitation reaction at a constant temperature of 90° C. The flow rate of the first solution and the second solution was 10 mL / min, and the pH of the reaction system was adjusted to 6 by ammonia water (mass concentration 25%), and aged for 2 h to obtain a precursor slurry;

[0091] Step (3): washing and filtering the precursor slurry, and vacuum drying at 110° C. for 18 h to obtain a magnesium-cobalt modified ferromanganese phosphate precursor;

[0092] Step (4): 0.1 mol and 0.11 mol of the precursor powder, 0.09 mol of lithium dihydrogen phosphate, and 0.03 mol of lithium carbonate were mixed evenly by ball milling at 400 rpm / 2 h, and then placed in a tubular furnace for calcination in two stages under an argon atmosphere, wherein the first calcination temperature was 450°C and the holding time was 4 h, and the second calcination temperature was 700°C and the holding time was 10 h. The heating rates of the two heatings were both 5°C / min, to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.

[0093] Example 4

[0094] This embodiment provides a method for preparing a magnesium-cobalt modified ferromanganese phosphate precursor and a carbon-coated lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0095] Step (1): according to the concentration of each raw material in the first solution being 0.3 mol / L manganese chloride, 0.19 mol / L ferrous sulfate, 0.01 mol / L magnesium sulfate and 0.05 mol / L ascorbic acid, each raw material is uniformly dispersed in water to obtain a first solution, and 85 wt.% phosphoric acid is uniformly dispersed in water to obtain a second solution with a concentration of 0.4 mol / L;

[0096] Step (2): 400 mL of the first solution and 606 mL of the second solution were respectively dripped into the reactor for a co-precipitation reaction at a constant temperature of 50° C. The flow rate of the first solution and the second solution was 25 mL / min. The pH of the reaction system was regulated to 6.5 by ammonia water (mass concentration 25%), and aged for 2 h to obtain a precursor slurry;

[0097] Step (3): washing and filtering the precursor slurry, vacuum drying at 110° C. for 18 h, mixing the dried precursor with 0.005 mol of cobalt tetroxide, and placing it in a tube furnace for annealing in an argon atmosphere at a temperature of 450° C. for 5 h and a heating rate of 5° C. / min to obtain a magnesium-cobalt modified ferromanganese phosphate precursor;

[0098] Step (4): 0.1 mol of the magnesium-cobalt modified manganese iron phosphate precursor and 0.1 mol of lithium dihydrogen phosphate, 0.1 mol of lithium carbonate and 0.02 mol of sucrose are mixed evenly by ball milling at 400 rpm / 2h and placed in a tubular furnace for calcination in two stages under an argon atmosphere, wherein the first calcination temperature is 350°C and the holding time is 4h, the second calcination temperature is 650°C and the holding time is 12h, and the heating rates of the two heatings are both 5°C / min, to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.

[0099] Comparative Example 1

[0100] The only difference between this comparative example and Example 1 is that magnesium sulfate and cobalt sulfate are not added in step (1).

[0101] Comparative Example 2

[0102] This comparative example provides a method for preparing a magnesium-cobalt modified ferromanganese phosphate precursor and a carbon-coated lithium manganese iron phosphate positive electrode material, comprising the following steps:

[0103] Step (1): according to the concentrations of the raw materials in the first solution being 0.3 mol / L manganese chloride, 0.2 mol / L ferrous sulfate and 0.05 mol / L ascorbic acid, the raw materials are uniformly dispersed in water to obtain a first solution, and 85 wt.% phosphoric acid is uniformly dispersed in water to obtain a second solution with a concentration of 0.4 mol / L;

[0104] Step (2): 400 mL of the first solution and 600 mL of the second solution were respectively dripped into the reactor for a co-precipitation reaction at a constant temperature of 50° C. The flow rate of the first solution and the second solution was 25 mL / min. The pH of the reaction system was regulated to 6.5 by ammonia water (mass concentration 25%), and aged for 2 h to obtain a precursor slurry;

[0105] Step (3): washing and filtering the precursor slurry, and vacuum drying at 110° C. for 18 h to obtain a magnesium-cobalt modified ferromanganese phosphate precursor;

[0106] Step (4): 0.1 mol of the magnesium-cobalt modified manganese iron phosphate precursor and 0.006 mol of magnesium sulfate, 0.004 mol of cobalt sulfate, 0.1 mol of lithium dihydrogen phosphate, 0.1 mol of lithium carbonate and 0.02 mol of sucrose are mixed evenly by ball milling at 400 rpm / 2h and placed in a tubular furnace for calcination in two stages under an argon atmosphere, wherein the first calcination temperature is 350°C and the holding time is 4h, the second calcination temperature is 650°C and the holding time is 12h, and the heating rates of the two heatings are both 5°C / min, to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.

[0107] Comparative Example 3

[0108] The only difference between this comparative example and Example 2 is that in step (2), aqueous ammonia is replaced by NaOH.

[0109] Comparative Example 4

[0110] The difference between this comparative example and Example 3 is that in step (4), the two-stage calcination method is changed to a single-stage calcination method, the temperature is 750° C., and the insulation time is 10 h.

[0111] Comparative Example 5

[0112] The difference between this comparative example and Example 4 is that the precursor after drying in step (3) is the final magnesium-cobalt-modified ferromanganese phosphate precursor, and no cobalt tetroxide is added and no annealing treatment is performed.

[0113] Structural characterization

[0114] Figure 1 is a SEM image of the magnesium-cobalt modified ferromanganese phosphate precursor obtained in Example 1; Figure 1 It can be seen that the particles present a nanoparticle morphology of uniform size.

[0115] Figure 2 is a SEM image of the carbon-coated lithium manganese iron phosphate obtained in Example 1; Figure 2 It can be seen that the particles present a micron-spherical morphology with uneven sizes.

[0116] Figure 3 is the XRD pattern of the carbon-coated lithium manganese iron phosphate obtained in Example 1; Figure 3 It can be seen that the diffraction peak position of the obtained carbon-coated lithium manganese iron phosphate is consistent with the characteristic diffraction peak of the standard card, indicating the successful synthesis of pure phase olivine crystal type lithium manganese iron phosphate.

[0117] Test Case

[0118] A lithium ion battery is prepared using the positive electrode materials of Examples 1 to 4 and Comparative Examples 1 to 5. The preparation method of the lithium ion battery comprises:

[0119] (1) Preparation of battery positive electrode

[0120] According to the mass ratio of 90:5:5, the positive electrode materials, conductive carbon black, and binder (PVDF) of Examples 1 to 4 and Comparative Examples 1 to 5 were weighed and fully ground and mixed, and then 4g of N-methylpyrrolidone was added to prepare a slurry. After stirring in a vacuum degassing machine, the black slurry was evenly coated on the aluminum foil using a slurry coater. The aluminum foil coated with the slurry was placed in a vacuum drying oven at 120°C and dried for 12 hours, then taken out, and after being rolled and compacted by an electric roller press, the aluminum foil coated with the slurry was cut into circular electrode sheets with a diameter of 13 mm using a slicer. The electrode sheet was vacuum dried at 110°C for 2 hours. After the water was fully dried, the mass of the electrode sheet was weighed using a precision balance, and numbered for standby use.

[0121] (2) Battery assembly

[0122] The half-cell uses an organic electrolyte. The metal lithium sheet is sensitive to oxygen and moisture. The assembly process of the half-cell is completed in a glove box filled with argon. The half-cell uses a 2032 button battery. Before use, the battery shell is cleaned with detergent, ultrapure water, and anhydrous ethanol in turn. A polypropylene film is used as a diaphragm. Before use, it is cut into a circular diaphragm with a diameter of 18mm using a slicer. A metal lithium sheet (Φ16*0.5) is used as the negative electrode of the button battery. The assembly process of the battery is as follows: flatten the lithium sheet, diaphragm, positive electrode sheet, gasket, spring and positive electrode shell in turn at the center of the negative electrode shell, and drip an appropriate amount of electrolyte on both sides of the diaphragm to moisten it. After assembly, the battery is packaged using a button battery packaging machine, and the corresponding electrochemical performance test is performed after standing for 12 hours.

[0123] The results are shown in Table 1.

[0124] Table 1 Battery performance test results of positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5

[0125]

[0126] It can be seen from Table 1 that the lithium manganese iron phosphate positive electrode materials prepared in Examples 1 to 4 of the present application have excellent gram capacity, electrical conductivity and cycle performance.

[0127] Comparison between Comparative Example 1 and Example 1 shows that no magnesium and cobalt elements were added for modification, which affected the electrical properties to a certain extent.

[0128] Comparison of Comparative Example 2 with Example 1: The addition of magnesium / cobalt to the subsequent firing of carbon-coated lithium manganese iron phosphate is not conducive to achieving atomic / molecular mixing of metal elements, thereby affecting the overall performance of the battery.

[0129] Compared with Example 2, Comparative Example 3 is as follows: the base type is changed to NaOH, and sodium ions are introduced, which occupy the lithium ion binding sites during the subsequent sintering of lithium manganese iron phosphate, affecting the binding of lithium ions and precursors, thereby affecting the structural stability of the formed positive electrode material, resulting in a lower gram capacity of the positive electrode material.

[0130] Comparative Example 4 is compared with Example 3: the two-stage calcination is changed to one-stage firing, and the carbon source decomposition and material formation are completed in one step, which is not conducive to the integrity of the lithium manganese iron phosphate lattice and the stability of the carbon coating structure, and affects the gram capacity and capacity retention rate.

[0131] Comparative Example 5 is compared with Example 4: the second cobalt source is not added for modification, and various properties are affected.

[0132] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A magnesium-cobalt modified ferromanganese phosphate precursor material, characterized in that: It comprises a ferromanganese phosphate matrix and magnesium and cobalt elements; the magnesium and cobalt elements are doped in the iron element sites in the ferromanganese phosphate matrix, or the magnesium element is doped in the iron element sites in the ferromanganese phosphate matrix and the cobalt element is coated on the outer layer of the ferromanganese phosphate matrix.

2. The method for preparing the magnesium-cobalt modified ferromanganese phosphate precursor material according to claim 1, characterized in that: The following steps are involved: mixing a metal source, an antioxidant and water to obtain a first solution; mixing a phosphorus source with water to obtain a second solution; The first solution, the second solution and an alkali solution are mixed to carry out a liquid phase coprecipitation reaction, and then aged to obtain a precursor slurry; Drying the precursor slurry to obtain a magnesium-cobalt modified ferromanganese phosphate precursor material; The metal source is a manganese source, a ferrous source, a magnesium source and a first cobalt source; or the metal source is a manganese source, a ferrous source and a magnesium source; When the metal source is a manganese source, a ferrous source and a magnesium source, after the precursor slurry is dried, the dried precursor is mixed with a second cobalt source, and annealed under a protective atmosphere to obtain a magnesium-cobalt modified manganese ferrophosphate precursor material.

3. The preparation method according to claim 2, characterized in that: The manganese source includes at least one of manganese sulfate, manganese chloride, manganese nitrate and manganese acetate; The ferrous source includes at least one of ferrous sulfate, ferrous oxalate and ferrous chloride; The magnesium source includes at least one of magnesium chloride and magnesium sulfate; The first cobalt source includes at least one of cobalt sulfate, cobalt chloride and cobalt nitrate; The second cobalt source includes at least one of cobalt oxide and cobalt tetroxide; The antioxidant comprises at least one of ascorbic acid, ascorbyl palmitate, erythorbic acid and sodium erythorbate; The phosphorus source includes at least one of phosphoric acid, diammonium hydrogen phosphate and diammonium dihydrogen phosphate; The molar ratio of the manganese source, the ferrous source, the magnesium source, the first cobalt source and the antioxidant is 2-8:1.7-7.9:0.1-0.3:0.1-0.3:1; the molar ratio of the manganese source, the ferrous source, the magnesium source, the second cobalt source and the antioxidant is 2-8:1.7-7.9:0.1-0.3:0.1-0.3:1; The molar ratio of the phosphorus source to the total moles of the manganese source, the ferrous source, the magnesium source and the first cobalt source is 1.1 to 1.3:1; The molar ratio of the phosphorus source to the total moles of the manganese source, the ferrous source, the magnesium source and the second cobalt source is 1.1-1.3:

1.

4. The preparation method according to claim 2 or 3, characterized in that: The temperature of the liquid phase coprecipitation reaction is 50-90° C., the pH value is 5-7, and the aging time is 2-4 hours.

5. The preparation method according to claim 4, characterized in that: The drying method is vacuum drying, the drying temperature is 80-110°C, and the drying time is 12-24h; The annealing temperature is 350-550° C., the holding time is 4-6 hours, and the heating rate to the annealing temperature is 5-10° C. / min.

6. Use of the magnesium-cobalt-modified ferromanganese phosphate precursor material according to claim 1 or the magnesium-cobalt-modified ferromanganese phosphate precursor material prepared by the preparation method according to any one of claims 2 to 5 in lithium iron manganese phosphate positive electrode materials.

7. A carbon-coated lithium manganese iron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: The magnesium-cobalt modified manganese iron phosphate precursor material is mixed with a lithium source, a phosphorus compound and a carbon source, and calcined under a protective atmosphere to obtain a carbon-coated manganese iron lithium phosphate positive electrode material; The magnesium-cobalt modified ferromanganese phosphate precursor material is the magnesium-cobalt modified ferromanganese phosphate precursor material according to claim 1 or the magnesium-cobalt modified ferromanganese phosphate precursor material prepared by the preparation method according to any one of claims 2 to 5.

8. The carbon-coated lithium manganese iron phosphate positive electrode material according to claim 7, characterized in that: The lithium source includes at least one of lithium phosphate, lithium dihydrogen phosphate, lithium hydroxide, lithium carbonate, lithium acetate and lithium oxalate, the phosphorus compound includes lithium phosphate or lithium dihydrogen phosphate, and the carbon source includes at least one of glucose, sucrose, citric acid, polyvinyl pyrrolidone, polyethylene glycol and ascorbic acid; The molar ratio of the magnesium-cobalt modified ferromanganese phosphate precursor material to the lithium source, the phosphorus compound and the carbon source is 1:(0.85-1.15):(0.85-1.15):(0.15-0.35); The mixing method is ball milling, the rotation speed of the ball mill is 350-500 rpm, and the ball milling time is 1.5-2.5 hours.

9. The carbon-coated lithium manganese iron phosphate positive electrode material according to claim 7, characterized in that: The calcination includes a first calcination and a second calcination performed sequentially; the temperature of the first calcination is 300-500°C, and the insulation time is 4-6 hours; the temperature of the second calcination is 550-750°C, and the insulation time is 10-12 hours; the heating rates of the first calcination and the second calcination are independently 5-10°C / min.

10. Use of the carbon-coated lithium manganese iron phosphate positive electrode material according to any one of claims 7 to 9 in a lithium ion battery.

Citation Information

Cited By

  • Lithium iron phosphate coated lithium-rich manganese-based material and preparation method thereof

    CN121416480A